ANALISIS RISIKO PENYEBAB KEBAKARAN DI MUSEUM RANGGAWARSITA DENGAN METODE LOSS CAUSATION MODEL - Vita Mardhiyanti Melati; Ekawati Ekawati; Bina Kurniawan; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2020)
The number of fire cases that hit museums, cultural heritage, and other historical buildings that are not known the main cause shows the lack of anticipating losses. Loss Causation Model is a theory of the causes of accidents which contains points and instructions used to understand the cause of an accident. The purpose of this study is to analyze the risk of fire in the Ranggawarsita Museum with the "Loss Causation Model" method. This research is a qualitative studied by conducting in-depth interviews with three  main informant and one triangulation informant. The results of this studied was indicated that the controlling factors in fire analysis were the unavailability of specific programs or program standards regarding fire. Basic cause in fire analysis were the lack of skills of workers that used of fire extinguisher for non-security and the lack of regular training that used of fire extinguisher for security. Immediate cause in the fire analysis was related to insecurity which consists of the average ignorance of workers on the policy both the efforts made by the museum in tackling fire emergencies, then unsafe condition in the form of a lack of attention in the installation of APAR and no other facilities of actived fire protection. The incident in the fire analysis was the occurrence of an electrical short circuit which can be handled appropriately by workers so as not to cause losses. Loss received in this fire analysis was absent. There was no fire at the Ranggawarsita Museum because the museum was able to deal with incidents quickly and precisely, but there was a small loss experienced by the museum that was damage to the museum facilities. There are weaknesses at every point in the Loss Causation Model theory that leads to the cause of an accident (fire).